Peran Senam Tiktok dalam Menjaga Kesehatan Fisik dan Mental Remaja - Putri, Ronasari Mahaji; Maemunah, Neni; Devi, Hilda Mazarina; Dewi, Novita; AP, Nurul (Jurnal Abdimas Kesehatan (JAK), 2025)
Gen Z is the nickname for today's young generation.  The various conveniences obtained as a result of advances in technology, transportation and household equipment have caused teenagers to become increasingly lazy about moving around. A comfortable, relaxed lifestyle, just sitting, lying down, watching television and playing on the phone, are the characteristics of the Sedentary lifestyle. Efforts are needed to encourage Gen Z to do physical activities. The aim of this community service is to provide knowledge, move teenagers physically and mentally through sweat-inducing tik tok exercises. With this sport packaged in the form of TikTok exercise, it is hoped that generation Z teenagers will be influenced to frequently move physically which will indirectly have a good influence on teenagers' health. The activity was attended by 91 teenagers, taking place at the Faculty of Health Sciences. The duration of the activity is 120 minutes, with a time allocation of 40 minutes (counseling) and 80 minutes of tik tok exercise. . It is hoped that this activity can continue and become a good habit for teenagers, so that the physical and mental health of teenagers is well maintained.